2014
DOI: 10.1111/ajo.12171
|View full text |Cite
|
Sign up to set email alerts
|

The use of 3‐dimensional ultrasound of the pelvic floor to predict recurrence risk after pelvic reconstructive surgery

Abstract: Aims: Female pelvic organ prolapse is a common condition. Prolapse recurrence following surgical treatment is a significant clinical issue. The aim of this study was to determine risk factors for recurrence, attempting to improve clinical practice by allowing better patient selection prior to surgery. Methods: This was a retrospective study utilising patient records and ultrasound volume imaging data sets obtained in four clinical audits following anterior colporrhaphy AE mesh. Prolapse recurrence was diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 33 publications
1
68
2
Order By: Relevance
“…It demonstrates excellent visibility of segments of the mesh between the vagina and bladder [6]. It has proven to be especially useful in diagnosing mesh folding or dislodgement [6] or in evaluating recurrent cystoceles after anterior colporrhaphy using alloplastic material [21, 22]. Because of its favorable cost/benefit ratio and the ability to do real-time viewing, we believe ultrasound will remain the main-stay for most clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates excellent visibility of segments of the mesh between the vagina and bladder [6]. It has proven to be especially useful in diagnosing mesh folding or dislodgement [6] or in evaluating recurrent cystoceles after anterior colporrhaphy using alloplastic material [21, 22]. Because of its favorable cost/benefit ratio and the ability to do real-time viewing, we believe ultrasound will remain the main-stay for most clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…While neurological, vascular and fascial damage may also be important in the pathogenesis of POP, one of the pathophysiological mechanisms seems to involve trauma to the levator ani muscle. Levator avulsion, a form of maternal injury in which the puborectalis becomes detached from the os pubis as a result of vaginal delivery, has been shown to be associated with anterior and central compartment prolapse and is a risk factor for prolapse recurrence. Diagnosis in the delivery room is usually impossible, as levator avulsion is commonly occult and difficult to assess even if exposed by vaginal tears.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this review suggest that there is no impact—improvement or deterioration—on PFM function as a result of POP/UI surgery. Given this, and the current lack of evidence to support perioperative PFM training, we may need to be guided by findings from studies that have shown a strong association between poorer preoperative PFM status and poorer postoperative PFM function . Therefore, focusing intervention on women with poor PFM function preoperatively, who are most likely to respond may be the best approach to achieve more effective outcomes from perioperative PFM interventions.…”
Section: Discussionmentioning
confidence: 99%